(untitled) (Harmoni, 2020)
Religious harmony is still being encouraged by the Indonesian government in the middle of some disharmony conditions in some areas. When the temple cliff in Pura Agung Arga Sunya in Krisik Village, Blitar was having landslide, the interfaith society helping hand in hand to get over it. It is interesting to find out the religious harmony model conducted by those interfaith society. This qualitative study was built based on the perception of the motives in having religious interfaith teamwork, local wisdom, also the actors and agents contestation. Using oral tradition and neo-ethnography analysis, this study try to explore the religious harmony practice around the Pura Arga Sunya Blitar, to find out the influenced factors of the harmony success, and to formulate the harmony model they used. First, the religious harmony practice in Krisik Village, which is potential to be latent conflict, still can be maintained by the society through strengthening the friendship and social brotherhood. Eventhough it seems to be just a pseudo-harmony, but it can fulfill enough the Indonesian religious society needs. Second, besides the religious doctrines, local wisdom has proven to have a significant role in maintaining religious harmony. Third, the religious model which can be adopted from them are: doing geographical and historical village awareness construction, strengthening and implementing local wisdom participation and role contestation in maintaining harmony, also creating and defining the harmony momentum.